2019
DOI: 10.3390/ijms20133251
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Colony Forming Cells as an Autologous Model to Study Endothelial Dysfunction in Patients with a Bicuspid Aortic Valve

Abstract: Bicuspid aortic valve (BAV), the most common congenital heart defect, is associated with an increased prevalence of aortic dilation, aortic rupture and aortic valve calcification. Endothelial cells (ECs) play a major role in vessel wall integrity. Little is known regarding EC function in BAV patients due to lack of patient derived primary ECs. Endothelial colony forming cells (ECFCs) have been reported to be a valid surrogate model for several cardiovascular pathologies, thereby facilitating an in vitro system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Recently, evidence of endothelial dysfunction (ED) present in BAV has surfaced ( Vaturi et al, 2011 ; Ali et al, 2014 ; Alegret et al, 2016 ; Gavriliuk et al, 2016 ; Balistreri et al, 2018 ; van de Pol et al, 2019 ). ED stands for the abnormal functioning of the endothelial cells (ECs) that cover the inner surface of blood vessels, the endothelium.…”
Section: Endothelial Dysfunction In Bav Disease: Evidence and Biomarkmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, evidence of endothelial dysfunction (ED) present in BAV has surfaced ( Vaturi et al, 2011 ; Ali et al, 2014 ; Alegret et al, 2016 ; Gavriliuk et al, 2016 ; Balistreri et al, 2018 ; van de Pol et al, 2019 ). ED stands for the abnormal functioning of the endothelial cells (ECs) that cover the inner surface of blood vessels, the endothelium.…”
Section: Endothelial Dysfunction In Bav Disease: Evidence and Biomarkmentioning
confidence: 99%
“…In this regard, our group discovered circulating endothelial microparticles (EMPs) – which are related to ED present in BAV patients plasma in higher concentrations than TAV, being also associated with aortic dilatation ( Alegret et al, 2016 ). Recent studies have shown impaired functionality or decreased number of endothelial progenitor cells (EPCs) in BAV ( Vaturi et al, 2011 ; van de Pol et al, 2019 ). Specifically, one group studieds functionality of peripheral blood endothelial colony-forming cells (pbECFCs) isolated from BAV patients compared to healthy ones as possible a biomarker ( van de Pol et al, 2019 ).…”
Section: Endothelial Dysfunction In Bav Disease: Evidence and Biomarkmentioning
confidence: 99%
See 2 more Smart Citations
“…Images were processed and analyzed in ImageJ (NIH, Bethesda, MD). Confocal images were converted to 500 ´ 500 pixel size, converted to binary, and circularity and area of cells, with an area of at least 50 µm 2 , well below the average size of ECFCs [19], were measured.…”
Section: Evaluation Of Cell Spreading Within Ipns Using Confocal Micrmentioning
confidence: 99%